When the clinic becomes a home. Successful VCT and ART services in a stressful environment - Jonathan Mensah Dapaah; Rachel Spronk (Taylor & Francis Group, 2016)
With the upscaling of antiretroviral therapy (ART) in resource-poor countries, many HIV-positive persons in Ghana have been accessing treatment in hospitals. Prevalence is relatively low compared to other African countries, 1.30%. HIV/AIDS remains heavily stigmatised in Ghana, which influences the provision and use of ART. This article investigates how HIV-positive persons accessing care and treatment go about their everyday lives in the ART clinic and how they have eventually come to see the clinic as a safe place that they call 'home'. The study took place in two Ghanaian hospitals in the Ashanti Region which in 2013 had the country's highest HIV prevalence rate of 1.30% [Ghana Health Service [GHS]/National AIDS Control Programme [NACP] (2013). 2013 HIV Sentinel Survey Report, Accra, Ghana]. It was conducted through ethnographic research, with data gathered in the two facilities through participant observation, conversations and in-depth interviews. It took place over a period of 15 months, between 2007 and 2010. In all, 24 health workers and 22 clients were interviewed in depth, while informal conversations were held with many others. The findings show that clients have adopted the clinic as a second home and used it to carry out various activities in order to avoid identification and stigmatisation as People Living with AIDS (PLWA). The most dramatic outcome was that, contrary to Ghanaian norms and values, people turned to non-kin for assistance. Accordingly, fellow clients and health personnel, rather than relatives, have become their 'therapy management group' [Janzen, J. M. (1987). Therapy Management: Concept, Reality, Process. Medical Anthropology Quarterly, 1(1), 68-84]. The clients have thus created a fictive family within the clinic - made up of health workers (as 'parents'), the clients themselves (as 'children') and the peer educators (as 'aunts' and 'uncles'). In the face of persistent stigma associated with HIV infection in Ghana, the use of the clinic as a 'home' has on the one hand helped those receiving treatment to maintain their position, respect and reputation within their families and community, while on the other it prevents PLWA from disclosing. The study concludes that compassion is an important element in the professionalisation of healthcare workers in low-prevalence countries.